Behavioral Activation Therapy to Reduce Withdrawal Behavior in Schizophrenia Patients - Karina, Tisa Alif; Ananta, Aliffia (Kirana Publisher (KNPub), 2024)
This study was motivated by observations on a subject who was a man with schizophrenia who was in a mental hospital ward. The subject had withdrawn behavior and did not want to mingle with friends there. If the subject's withdrawn behavior is not handled, it will hinder the subject's treatment because the subject does not want to do anything other than lie in bed and stay in the corner of the room. The purpose of this study was to reduce withdrawn behavior by increasing the subject's involvement in daily activities. This study used an experimental design in the form of a single-subject study. The data collection technique used in this study was to measure behavior to assess whether the subject was involved in scheduled activities. Data analysis used a monitoring sheet to see behavior before and after the intervention. The results showed that the Behavioral Activation Therapy (BAT) technique given was quite successful, as seen from the subject who was willing to do several scheduled activities so that it could reduce withdrawn behavior.